KAJIAN TEORETIS INTEGRASI MODEL MULTIPLE INTELLIGENCES DAN EXPERIENTIAL LEARNING DALAM PEMBELAJARAN - Ismail (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2026)
Conventional learning practices tend to ignore the diversity of students' intellectual potential and focus solely on strengthening academic abilities, resulting in suboptimal holistic talent development. This study aims to examine the application of the Multiple Intelligences and Experiential Learning models in the learning process and identify the effectiveness of integrating the two in creating adaptive, student-centered learning. This study uses a literature review method with a descriptive-conceptual design through the exploration of academic literature analyzed using descriptive-comparative content analysis techniques, including the identification of key concepts, classification of thematic information, comparison of views between sources, and synthesis of information to construct a coherent theoretical framework. The findings of this study indicate that mapping multiple intelligences helps teachers understand the individual characteristics of students and adjust learning strategies, while authentic experiences through Experiential Learning can improve conceptual understanding and foster active attitudes. The synergy of the two models creates more inclusive, participatory learning and optimizes the balanced cognitive, affective, and psychomotor development of students, making it a suitable reference for designing humanistic learning that is relevant to the developmental needs of contemporary students.